Mapping climate change impacts on the distribution and conservation status of key indigenous medicinal plants in south Africa. A cross-sectional GIS-based spatial analysis. - Mbanjwa, Sibonelo Thanda (Student's Journal of Health Research Africa, 2026)
Background Indigenous medicinal plants are central to primary healthcare, cultural practices, and biodiversity conservation in South Africa. Climate change, characterised by rising temperatures, shifting rainfall regimes, and recurrent droughts, poses increasing risks to their distribution and conservation status. Spatial evidence on how climate variability affects key medicinal plant species remains limited. This study mapped climate change impacts on the distribution and conservation status of selected indigenous medicinal plants to inform climate-responsive conservation planning. Methods A cross-sectional GIS-based spatial analysis was conducted using species occurrence records obtained from national biodiversity databases, herbarium collections, and published sources. Climate variables, including mean annual temperature and precipitation, were derived from established climate datasets. Spatial modelling was applied to assess current distribution patterns, climate suitability, and vulnerability hotspots. Results The analysis identified measurable contractions and altitudinal shifts in climatically suitable habitats for several species, including Artemisia afra, Aloe ferox, Warburgia salutaris, and Siphonochilus aethiopicus. Habitat suitability declined by 18–35% in interior provinces experiencing warming trends exceeding 1.5 °C over recent decades. Approximately 42% of identified high-risk vulnerability hotspots were located outside formally protected areas, increasing exposure to land-use pressures. Species already listed as Vulnerable or Endangered showed higher overlap with areas of projected climatic stress, with up to 30% of their current distribution ranges falling within high-temperature and low-rainfall zones. Conclusion Climate change is reshaping the spatial distribution and increasing the conservation vulnerability of indigenous medicinal plants in South Africa. GIS-based spatial analysis provides actionable evidence for identifying at-risk species and priority intervention areas. Recommendations. Climate adaptation should be integrated into biodiversity management frameworks, with expanded protection in identified hotspots, strengthened sustainable harvesting regulation, and long-term monitoring of climate–biodiversity interactions.